Peranan audit kinerja dalam meningkatkan efisiensi dan efektivitas Bandung Urban Development Project - A Rodi Kartamulja (Jurnal Akuntansi dan Auditing Indonesia, 2001)
The intensification of development by government in general and by the Bandung Urban Development Project (BUDP) in particular requires an intensification of performance auditing is necessary with emphasis on compliance, efficiency, and effectiveness of the development program and operational activities. This the writer’s basic idea on the research of the role of performance auditing in improving the efficiency and effectiveness of the BUDP.The model uses performance auditing as independent variable and the rate of efficiency and effectiveness of using BUDP II project funds as dependent variables. The criteria of management auditing and of those programs at the seven sectors above have reached more than 75%. On the other hand, the average scores of management auditing, and program auditing are 85,08% and 83,39% of the total maximum score of 148 (100%).According to the results, the coefficient is reliable and valid by using 3 sample and 2 auditors from each sector and questionnaire (r) of 37 items, and by the use of Spiergelman’s theory of assumed validity and reliability. Although each coefficient of the management and the program auditing, has the lower grade of 10% and 33,5% performance auditing, based on questionnaires (100% replies answered “Yes”) and the relationship and ranking score between two variables are the extreme values of B and C.Spearman’s method used to test the rank correlationship between the rate of fulfillment criteria of performance auditing and the rate of  efficiency and effectiveness, whose result tends to be positive between the two variable factors, where : calculated rs s ³ 0,714, at confidence level of 95% (a = 0,05).The empirically based hypothesis  can be tested by measuring the method’s reliability coefficient of any sector and unit, and by testing the seven sector in to canonical table of the BUDP II